Economic Regimes in the Long Decolonization of Indonesia: The Nexus between State and Business, 1930s-1950s - Remco Raben (Universitas Gadjah Mada, 2013)
This article discusses the relationship between private business and government during both the late-colonial period and the immediate post-independence era. Special attention is given to the chaotic conditions during the Indonesian Revolution in the second half of the 1940s. The article argues that the relationship was strong in both periods but of a fundamentally different nature after independence as compared to Dutch colonial rule. The colonial system of institutionalized business interests was not taken over by the Indonesian nationalists. The colonial system was replaced by a system in which privilege strongly depended on political connections, favouring some, but not all businessmen. Further research is needed to unveil the specifc nature of relationships between private businessmen and the Indonesian state.